TathbiquLu’batu Al Hims Al Mutasalsil Li At Tarqiyati Maharati Al Istima’ fi MA Bilingual Batu - faiz, nur (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Abstrac The role of language games in the learning process can help teachers achieve better language learning goals. Students become more enthusiastic and less bored. Not only improve intellectual abilities but also social skills. In this game, students do not only focus on listening skills but also on speaking and writing skills and even reading. This article aims to improve students' listening skills with the Whisper Chain game. This research uses a qualitative and field approach in MA Bilingual. The results of the study show the application of the Whisper Chain game as follows: giving vocabulary, listening to reading texts, discussing difficult vocabulary, and finally evaluating and strengthening the material using games. By implementing the Whisper Chain game: 1) Can improve students 'listening skills effectively because it is more applicable as well as students memorize verbal vocabulary, 2) Increase students' social intelligence and increase their attention in learning, 3) Make it easier for students to better understand the material and provide learning experiences. Keywords : Listening Skill, Whisper Chain Game Abstrak Peran permainan bahasa dalam proses kegiatan belajar dapat membantu guru dalam mencapai tujuan pembelajaran bahasa yang lebih baik. Siswa menjadi lebih semangat dan tidak bosan. Tidak hanya meningkatkan kemampuan intelektual namun juga kemampuan sosial. Dalam permainan ini, siswa tidak hanya fokus pada kemampuan mendengarkan saja namun juga pada kemampuan berbicara dan menulis bahkan membaca. Artikel ini bertujuan untuk meningkatkan kemampuan menyimak siswa dengan permainan Bisik Berantai. Penelitian ini menggunakan pendekatan kualitatif dan lapangan di MA Bilingual. Adapun hasil penelitian menunjukkan penerapan permainan Bisik Berantai sebagai berikut : pemberian mufrodat, mendengarkan teks bacaan, membahas kosa kata sulit yang terakhir evaluasi dan penguatan materi menggunakan permainan. Dengan menerapkan permainan Bisik Berantai : 1) Dapat meningkatkan ketrampilan mendengarkan siswa secara efektiv karena lebih aplikatif sekaligus siswa menghafalkan kosa kata verbal, 2) Meningkatkan kecerdasan sosial siswa serta menambah perhatian mereka dalam pembelajaran, 3) Memudahkan siswa untuk lebih memahami materi dan memberikan pengalaman belajar. Kata kunci : Ketrampilan Menyimak, Permainan Bisik Berantai